2018
DOI: 10.1590/0103-8478cr20180047
|View full text |Cite
|
Sign up to set email alerts
|

P wave dispersion in obese dogs with and without mitral valve disease

Abstract: Pwave dispersion (Pd) is an electrocardiographic index defined as the difference between the minimum and maximum Pwave duration in multiple leads. The augmentation of Pd reflects the discontinuous and inhomogeneous atrial depolarization resulting from cardiac and non-cardiac conditions. In humans, an increased Pd is associated with the development of cardiac arrhythmias, particularly atrial fibrillation. To investigate Pd in obese dogs, we enrolled 76 dogs, which were classified in four distinct categories acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The associations with sex and bodyweight in human patients have been suggested to be related to atrial size since increased bodyweight is one of the most important determinants of atrial size [ 72 ] and males tend to be heavier than females. In dogs, increased Pd has also been associated with greater bodyweight but not sex differences [ 42 ]. We found no significant association between age, sex or bodyweight and P wave duration or dispersion in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The associations with sex and bodyweight in human patients have been suggested to be related to atrial size since increased bodyweight is one of the most important determinants of atrial size [ 72 ] and males tend to be heavier than females. In dogs, increased Pd has also been associated with greater bodyweight but not sex differences [ 42 ]. We found no significant association between age, sex or bodyweight and P wave duration or dispersion in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have reported the use of P wave indices in veterinary medicine [ 37 , 38 , 39 , 40 , 41 , 42 ]. In dogs, Pd has been shown to be significantly increased in those with chronic valvular disease and disturbances of supraventricular conduction [ 38 , 42 ] and was also found to be a useful predictor of arrhythmia recurrence following electrical cardioversion of AF [ 39 ]. In horses, only one study has been performed to determine the values of Pd in healthy Silesian and Polish primitive horses [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the related clinical the risk of, e.g., supraventricular arrhythmias in dogs (Noszczyk-Nowak et al 2008). This indicator is used to evaluate atrial arrhythmias and atrial fibrillation in human medicine (Dilaveris and Gialafos 2001); it is a novel tool in veterinary medicine to follow a chronic valvular disease (Noszczyk-Nowak et al 2011), in obese dogs with and without mitral valve disease (Dittrich et al 2018), and atrial fibrillation (Noszczyk-Nowak 2012). To our knowledge, only one study including P d alteration associated with CVL has been reported with increasing P d values in polysymptomatic dogs (Nakipoglu and Ural 2018).…”
mentioning
confidence: 99%